MATURE SOCIAL ECONOMY ENTERPRISE AND SOCIAL INNOVATION: THE CASE OF THE DESJARDINS ENVIRONMENTAL FUND. (25th April 2017) - VÉZINA, Martine; MALO, Marie‐Claire; BEN SELMA, Majdi
ABSTRACT: This study seeks to understand the nature and process of social innovation driven by mature social economy enterprises, and the innovative capability that supports it. The research examines enterprise capabilities by means of the institutional approach to social innovation and the Resource‐Based View theory (RBV). Based on grounded theory, this research focuses on a single case, the creation of the Desjardins Environment Fund (DEF). Launched 25 years ago, 1 DEF is the first mutual fund in North America to include extra‐financial criteria in its evaluation of business environmental management practices (fund securities) for the information of individual investors. The findings of this empirical research show how a major cooperative bank can generate social innovation and how this entails organizational innovations. The findings also reveal how these innovations benefit from the strategic and process resources that the Desjardins Movement managed to develop while taking into account both its core business (as a bank) and its purpose (as a cooperative). This study shows that the innovative potential of the mature social economy enterprise should not be underestimated.